Review: Catalytic oxidation of cellulose with nitroxyl radicals under aqueous conditions. (November 2018) - Isogai, Akira; Hänninen, Tuomas; Fujisawa, Shuji; Saito, Tsuguyuki
Graphical abstract: Abstract: 2, 2, 6, 6-Tetramethylpiperidine-1-oxyl radical (TEMPO)-mediated oxidation is a unique reaction to native and regenerated celluloses, and has advantages in terms of position-selective reaction at room temperature under aqueous conditions. When the TEMPO/NaBr/NaClO oxidation is applied to native celluloses in water at pH 10 under suitable conditions, the C6-primary hydroxy groups present on crystalline cellulose microfibril surfaces are mostly converted to sodium C6-carboxylate groups. Anionic sodium glucuronosyl units are densely, regularly, and position-selectively formed on crystalline cellulose microfibril surfaces, while maintaining the original cellulose morphology, cellulose I crystal structure, crystallinity, and crystal width. When TEMPO-oxidized celluloses (TOCs) prepared from, for example, wood cellulose have sodium C6-carboxylate contents >1 mmol/g, transparent highly viscous gels consisting of TEMPO-oxidized cellulose nanofibrils (TOCNs) with homogeneous widths of ≈3 nm and lengths >0.5 μm, dispersed at the individual nanofiber level, are obtained by gentle mechanical disintegration of TOCs in water. Alternative systems are as follows: TEMPO/NaClO/NaClO2 system, TEMPO electro-mediated oxidation, etc. TOCNs are promising new plant-based renewable nanofibers applicable to high-tech material fields.